Lexical Choice and Rhetorical Expression: Comments By Peter Feldmeier (American Journal of Islam and Society, 2018)
Many religions understand themselves as fundamentally aligned to a givenculture or people. Hinduism is intrinsically connected to the Indian cultureand caste system. Daoism and Confucianism are highly integrated into theChinese spirit and the cultural mentality of the Orient. Shinto’s cosmology,myths, and rites concern themselves solely with the Japanese. Even in theWest, Judaism locates itself with the people of Israel. Jews welcome converts,but Judaism has never seen itself as a proselytizing religion. Islamis convinced that Muhammad’s message is both universal and constitutesthe highest revelation. Thus, it is a proselytizing religion. But Muslims historicallyand today believe that non-Muslims can be saved in the contextof their own religious traditions, particularly if these are monotheistic.Christianity perhaps stands alone as a religion that has historically believedthat membership in the church is necessary for salvation. Add to this thatRoman Catholicism had believed that Catholic membership was necessary.As the Fourth Lateran Council (1215) declared, “There is only one universalchurch of the faithful, outside which none can be saved.” More recently,most Christians, including Catholics, think that God’s saving grace is availableoutside its ecclesial boarders, but this is a modern idea.What then to think of the religious other? In the seventeenth century,a Catholic had few conceptual choices. One was to consider religious othersand their sacred texts as valuable preparation for the gospel, and thusadmire what could be admired in them. They had something of what St.Justin Martyr called the Logos spermatikos, seeds of the Word. This includedthe principle of inculturation whereby European culture was not to beconflated with Christianity. This principle became policy, at least in theory, ...